Pemikiran Hadis Ahmad Hassan tentang Hadits di Indonesia - Rohman, Teguh Abdul; Arifin, Tajul (Asian Journal of Islamic Studies and Da'wah, 2025)
A. Hassan encouraged efforts to perform ijtihad by referring to the Qur'an and Sunnah. Hassan's call to directly base one's views on the Qur'an and Sunnah motivated people to study the sciences related to these two sources, particularly hadith and the science of hadith. The purpose of this written work is to understand A. Hassan's approach to the study of hadith, including his research methodology as well as his critique of sanad (chain of transmission) and matan (content). The methodology used is specifically descriptive analysis, which involves studying specific objects, conditions, or phenomena and aims to provide a systematic, factual, and accurate general description. As a scholar of hadith, it is essential to study A. Hassan's thoughts, as the motto ar-ruju’ ila Qur’an wa Sunnah (returning to the Qur'an and Sunnah) cansnot be separated from his significant contributions.